2015
DOI: 10.1039/c5dt02912k
|View full text |Cite
|
Sign up to set email alerts
|

Brønsted acid-promoted C–F bond activation in [P,S]-ligated neutral and anionic perfluoronickelacyclopentanes

Abstract: Treatment of L2Ni(CF2)44a-c (L = PPh3, PPh2Me, pyridine) with an external Lewis acid (trimethylsilyl triflate) gives new L-functionalized fluoronickelacyclopentanes 5a-c. Complexes L2Ni(CF2)44a,b react with the thiol form of the bidentate ligand 1,2,4-(HS)(Ph2P)Me(C6H3) [P,SH] through a unique Brønsted acid-promoted Cα-F bond activation mechanism, affording phosphine-functionalized nickelacycles bearing a phosphinothiolate ligand 6a-b. Furthermore, substituting monodentate ligands in L2Ni(CF2)44a-c with the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 49 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…31,32,80 The replacement of fluorine in poly-or perfluorinated molecules by a new functional group in order to obtain a higher valuable fluorinated building block still remains rare and challenging. 18,27,[80][81][82] In previous work we demonstrated that the rhodium complexes [Rh(H)(PEt 3 ) 3 ] (3) or [Rh{(Z)-CFvCF(CF 3 )}(PEt 3 ) 3 ] are suitable for a catalytic C-F bond transformation of hexafluoropropene in the presence of HBpin ( pin = pinacolato) or tertiary silanes to afford fluoroalkyldioxaborolanes or 3,3,3-trifluoropropylsilanes, respectively. 78,79 Note that not in any of these cases a C-F activation and functionalization of the trifluoromethyl group was observed.…”
Section: Introductionmentioning
confidence: 99%
“…31,32,80 The replacement of fluorine in poly-or perfluorinated molecules by a new functional group in order to obtain a higher valuable fluorinated building block still remains rare and challenging. 18,27,[80][81][82] In previous work we demonstrated that the rhodium complexes [Rh(H)(PEt 3 ) 3 ] (3) or [Rh{(Z)-CFvCF(CF 3 )}(PEt 3 ) 3 ] are suitable for a catalytic C-F bond transformation of hexafluoropropene in the presence of HBpin ( pin = pinacolato) or tertiary silanes to afford fluoroalkyldioxaborolanes or 3,3,3-trifluoropropylsilanes, respectively. 78,79 Note that not in any of these cases a C-F activation and functionalization of the trifluoromethyl group was observed.…”
Section: Introductionmentioning
confidence: 99%
“…[31] Fluorinated metallacyclopentanes have been obtained by cyclodimerization of fluorinated ethenes (F), [22,[32][33][34][35][36][37][38] or cocyclodimerization of C 2 F 4 and C 2 H 4 (G), [39,40] on electron-rich metal centres. Their unusual reactivity [41][42][43][44] illustrates the potential of C 2 F 4 in the synthesis of valuable fluoroorganic compounds. [37,39,40] Only a few perfluorometallacycles with n ¼ 6 4 have been reported.…”
mentioning
confidence: 99%
“…Therefore, the ring-closing reaction described in eq can proceed in good yield (75%) without the need for any CsF salt additives. When the reaction described in eq is monitored by 19 F NMR spectroscopy, the fate of the metal complex after the reaction is [(pyr) 2 Ni­(C 4 F 8 )] (97% after 18 h at room temperature). …”
mentioning
confidence: 99%